The Shareholder Base and Payout Policy - Bodnaruk, Andriy; Östberg, Per (Journal of Financial and Quantitative Analysis, 2013)
Abstract We examine the relation between the shareholder base and payout policy. Consistent with the idea that the shareholder base is related to the cost of external financing, we find that firms with small shareholder bases have lower payout levels and maintain higher cash holdings. We show that undertaking an open market repurchase results in a significant reduction in the size of the shareholder base. Consequently, we find that firms with small shareholder bases are less likely to undertake a repurchase (reduce the shareholder base even further) and are more likely to pay special dividends.